Factors Influencing the Choice of Commercial Bank among Transport Workers in Anambra State Nigeria - Ezeh, Precious; C. Nwaizugbo, Ireneus (British Journal of Marketing Studies, 2016)
This study was conducted to identify the factors (technical, functional and environmental) that influence the bank selection decision of transport workers in Awka, Anambra State. Competition in banking sector is increasing day by day and this forces the banking sector to identify and satisfy new markets to increase their customer base and market share. Data were collected through self-administered questionnaire to three hundred (300) transport workers in Awka environment, capital of Anambra State. Descriptive statistics and ANOVA were used to analyze data. Out of twenty eight (28) factors studied it was found out that secure feeling, bank reputation, continuous information flow, efficient service and confidentiality are the most important influencing factors in choosing a bank among the transport workers in Awka, Anambra State Nigeria. Using the three dimensions of services factors, that is, technical, functional and environmental; it shows that technical factors have significant influence, followed by functional factor, while Environmental factors have no significant influence on transport workers. We recommend that banks located in Awka, Anambra State that wants to serve the transport workers should consider the five most important factors as an invaluable strategic tool for marketing strategy design. They should emphasis more on what the customer received, than the way in which the service is deliver and the physical environment of the bank.